2015
DOI: 10.1177/0093650215601883
|View full text |Cite
|
Sign up to set email alerts
|

Explicating Net Diversity in Trend Assessment

Abstract: This study tracks the increasing supply of Internet access and the diversity of Internet use by analyzing data from the three waves of a survey conducted in the United Kingdom in 2005, 2007, and 2009. Data on Internet access and three dimensions of online use (civic-government, economic-commerce, and generic information and news) reveal that the Internet not only offers an emergent promise of diversity but also presents a systematic divide in which the increase in benefits (of Internet capacities and actual co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
11
2
Order By: Relevance
“…Thus, for example, she demonstrated that younger and more educated participants are better at retrieving information online (Hargittai, 2002), and younger adults coming from more educated households and those identifying as either Asian American or White, are likelier to have both better access to technology and stronger DLS (Hargittai & Hinnant, 2008). Today, there is a body of work demonstrating a persistent relationship between income, education, race, and age, and inequalities in DLS (e.g., Park, 2018b; van Deursen & van Dijk, 2015; van Dijk, 2005; van Dijk & Hacker, 2003).…”
Section: Digital Dividementioning
confidence: 99%
“…Thus, for example, she demonstrated that younger and more educated participants are better at retrieving information online (Hargittai, 2002), and younger adults coming from more educated households and those identifying as either Asian American or White, are likelier to have both better access to technology and stronger DLS (Hargittai & Hinnant, 2008). Today, there is a body of work demonstrating a persistent relationship between income, education, race, and age, and inequalities in DLS (e.g., Park, 2018b; van Deursen & van Dijk, 2015; van Dijk, 2005; van Dijk & Hacker, 2003).…”
Section: Digital Dividementioning
confidence: 99%
“…In summary, the literature on social stratification emphasizes the socialization process in the adoption and the use of new technologies (DiMaggio et al, 2001; Neuman et al, 2011; Park, 2013, 2015a, 2015b; Park and Yang, 2017; Rogers, 2010). A logical extension is that those in socially privileged positions would be more politically socialized and more competent in dealing with new technologies, such as social media networks, and with the costs and benefits involved in revealing one’s political values.…”
Section: Addressing Existing Gapsmentioning
confidence: 99%
“…education, income, age), as well as social environment, impact how people consume and use Google platforms (Bucy, 2000;Park, 2015;Park, Jang, Lee & Yang, 2018). For example, Park (2015) analyzed data from the three waves of a survey conducted in the U.K. and demonstrated that the social background of users impact their Internet use. Those from underserved communities had lower access to the Internet and were significantly behind others in their use of the Internet for commerce.…”
Section: Discussionmentioning
confidence: 99%